Trends and Future Directions in Tax Policy Reform : A Latin American Perspective - Shome, Parthasarathi (IMF Working Papers; Working Paper ;, 1992)
Tax reform in Latin America during the 1980s emphasized broad-based, low-rate consumption taxes over steeply progressive income and property taxes, primarily to simplify the tax structure and facilitate tax administration. While tax reform need not necessarily raise tax-to-GDP ratios, countries that undertook tax reform experienced a higher revenue gain in terms of GDP relative to those that did not. Tax reform issues during the 1990s will include a minimum income tax, alternative corporate taxes (cash flow tax, assets tax), capturing difficult tax bases (financial intermediation, property), environment taxes, extending withholding as a taxing mechanism, and tax harmonization.